Value of tomosynthesis for lesion evaluation of small joints in osteoarthritic hands using the OARSI score. Issue 7 (July 2016) - Martini, K.; Becker, A.S.; Guggenberger, R.; Andreisek, G.; Frauenfelder, T.
Summary: Objective: To determine the diagnostic performance of tomosynthesis in depicting osteoarthritic lesions in comparison to conventional radiographs, with use of computed tomography (CT) as standard-of-reference. Methods: Imaging of 12 cadaveric hands was performed with tomosynthesis in dorso-palmar (dp) projection, conventional radiographs (dp) and multi-detector CT. Distal interphalangeal joint (DIP)II, DIPIII, proximal interphalangeal joint (PIP)II, PIPIII, first carpometacarpal (CMC) and scaphotrapezotrapezoidal joint (STT) were graded by two independent readers using the Osteoarthritis Research Society International (OARSI) score. The mean score for each feature was calculated for all modalities. Additional wrists were evaluated for presence of calcium pyrophosphate disease (CPPD). CT served as reference-standard. Inter-reader agreement (ICC) was calculated. Results: Comparing tomosynthesis and conventional radiographs to CT, the sensitivity for the presence of osteophytes was 95, 7% vs 65, 2%; for joint space narrowing 95, 8% vs 52, 1%; for subchondral sclerosis 61, 5% vs 51, 3%; for lateral deformity 83.3% vs 83, 3%; and for subchondral cysts 45, 8% vs 29, 2%. Erosions were not present. While tomosynthesis showed no significant difference in OARSI score grading to CT (mean OARSI-score CT: 16.8, SD = 10.6; mean OARSI-score Tomosynthesis: 16.3, SD = 9.6; P  = 0.84), conventional radiographs had significant lower mean OARSI scores (mean OARSI-score X-ray: 11.1, SD = 8.3; P  = 0.04). Inter-reader agreement for OARSI scoring was excellent (ICC = 0.99). CPPD calcifications present in CT, were also visible with tomosynthesis, but not with conventional radiography. Conclusion: In conclusion, tomosynthesis depicts more osteoarthritic changes in the small joints of the hand than conventional radiography using the OARSI scoring system and CT as the standard of reference.